RAISING THE INNOVATIVE THINKING OF STUDENT-YOUTH - Karimova Muyassarkhon Abdukayumovna; Karimov son of Muhammadrakhim Salimjon (Galaxy International Interdisciplinary Research Journal, 2023)
In this article, a new paradigm of social production efficiency growth is formed based on the use of knowledge and innovation as the most important sources of economic resources in the global globalization system. It requires the development of a system of integrated views that will become the philosophical basis for the formation of the innovative development strategy of the country.